Motivasi Berprestasi Guru Agama Hindu Jenjang SMP Yang Sudah Bersertifikat Pendidik - I Made Wiguna Yasa; I Komang Wisnu Budi Wijaya; Gusti Ayu Agung Riesa Mahendradhani; Ni Kadek Supadmini (Jayapangus Press, 2020)
This study aimed to describe the level of achievement motivation Hindu religious teachers are certified educators. This research belongs to qualitative research. The population of this study were teachers of Hindu religious subjects at Junior High School who were certified educators in Tabanan Regency. Samples were taken using saturated sampling techniques. The research instrument used was achievement motivation questionnaire. The questionnaire was tested for validity and reliability. Data were analyzed descriptively. The results showed that 8.7% of teachers had very high achievement motivation; 76.1% had high achievement motivation and 15.2% had achievement motivation level in the sufficient category. The achievement motivation of these teachers is influenced by factors such as job satisfaction, appreciation, physical and social environment and the existence of career paths.